Inclusive citizenship: meanings and expressions / edited by Naila Kabeer - "Kabeer, Naila (ed.)" (New Delhi, 2005)
Attempts to go beyond the intellectual debates of recent years on democratization and participation to explore a related set of issues around changing conceptions of citizenship.
Keywords: Citizenship